PERAN MEDIA SOSIAL DALAM PERKEMBANGAN BUDAYA OLAHRAGA MODERN : PERSPEKTIF SOSIOLOGI OLAHRAGA - Siregar, Yan Indra; Arima, Putra; Hasibuan, Nabila Bilqis; Saragih, Zefta Exaudy; Rumahorbo, Johan Agung Adrian; Sirait, Tono Bonardo; Siadari, Micael Rafael; Girsang, Suranta Juli Kipli; Hura, Irvan Gunawan; Lumbantobing, Jeremi Hasiholan Asido (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study discusses the role of social media in the development of modern sports culture from the perspective of sports sociology. The development of digital technology has made social media one of the important factors influencing people's interaction patterns with sports. Social media functions not only as a means of communication and entertainment, but also as a social space in shaping lifestyles, group identities, and modern sports culture. This research uses a literature study method with a qualitative approach sourced from national journals and various scientific references published within the last ten years. The results show that social media has a major role in increasing the popularity of sports, building digital sports communities, strengthening relationships between athletes and fans, and increasing public awareness of the importance of healthy living. However, social media also creates negative impacts such as excessive fanaticism, digital conflicts among supporters, and image-building culture in sports. Therefore, the use of social media needs to be directed positively in order to support the development of a healthy, educational, and socially constructive sports culture in the modern era.